2006
DOI: 10.1103/physrevlett.97.080403
|View full text |Cite
|
Sign up to set email alerts
|

Stable Skyrmions in Spinor Condensates

Abstract: Globally symmetric spinor condensates in free space are argued not to support stable topological defects in either two or three dimensions. In the latter case, however, we show that a topological Skyrmion can be stabilized by forcing it to adopt certain density profiles. A sufficient condition for the existence of Skyrmion solutions in three dimensions is formulated and illustrated in simple examples. Our results pertain to Bose-Einstein condensation in 87Rb.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
460
2
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 248 publications
(483 citation statements)
references
References 23 publications
20
460
2
1
Order By: Relevance
“…3 In all these cases, the linearly dispersing Dirac quasiparticles give rise to a semimetallic ground state, stable against weak electronelectron interactions. 4 When the repulsive interactions are sufficiently strong, however, a plethora of insulating phases can in principle be realized in graphene. [4][5][6] Furthermore, Dirac fermions in graphene can also condense into four different gapped superconducting states, if the net interaction acquires an attractive component.…”
mentioning
confidence: 99%
“…3 In all these cases, the linearly dispersing Dirac quasiparticles give rise to a semimetallic ground state, stable against weak electronelectron interactions. 4 When the repulsive interactions are sufficiently strong, however, a plethora of insulating phases can in principle be realized in graphene. [4][5][6] Furthermore, Dirac fermions in graphene can also condense into four different gapped superconducting states, if the net interaction acquires an attractive component.…”
mentioning
confidence: 99%
“…[4,5,6,7,8,9,10,11,12,13,14,15,17,16]). There, the predominant ordering tendencies are in the particle-hole channel, and usually superconductivity is not among the leading candidates.…”
Section: Undoped and Weakly Doped Graphenementioning
confidence: 99%
“…A large number of exotic states of matter has been proposed theoretically, see e.g. [4,5,6,7,8,9,10,11,12,13,14,15,16,17], but most have not been experimentally observed as of yet. One exception is multi-layer graphene systems where there are now experimental reports of an energy gap opening at low temperatures, which has been ascribed to interactions effects [18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…20 Extensive studies on interacting graphene have shown a variety of competing phases. [22][23][24] Below we discuss the effects of producing the longer range interactions required for topological order using the Friedel oscillations and Ruderman-Kittel-Kasuya-Yosida (RKKY) interactions occurring in a metallic (Fermi-gas) environment. Our analysis considers the possibility of forming both topological phases as well as other competing phases.…”
Section: Introductionmentioning
confidence: 99%